2010
DOI: 10.1007/s00466-010-0489-x
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the equilibrium position of a liquid with surface tension inside a tank of complex geometry and extension to sloshing dynamic cases

Abstract: To study the vibrations of a tank partially filled with a liquid in low-gravity environment, we first have to find the static position of the liquid. In this paper, we present a three-dimensional finite element approach to find this equilibrium configuration for any tank geometry. Both gravity and capillary effects are taken into account. The nonlinear equations of this problem are derived from the differentiation of the total potential energy of the system, then the problem is transformed into a liquid free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Concerning the definiteness of K : Let us first remark that the dynamic stiffness operator is very similar to the tangent stiffness operator established in the previous paper dealing with the static computation [4] (except for the effect of the tank wall curvature in K that has been neglected in the static computation). In that paper, it has been shown that this stiffness operator is singular due to the well-known 'lack of rigidity' in the tangent direction to the free surface plane [13,14].…”
Section: El-kamali J-s Schotté and R Ohayonmentioning
confidence: 95%
See 4 more Smart Citations
“…Concerning the definiteness of K : Let us first remark that the dynamic stiffness operator is very similar to the tangent stiffness operator established in the previous paper dealing with the static computation [4] (except for the effect of the tank wall curvature in K that has been neglected in the static computation). In that paper, it has been shown that this stiffness operator is singular due to the well-known 'lack of rigidity' in the tangent direction to the free surface plane [13,14].…”
Section: El-kamali J-s Schotté and R Ohayonmentioning
confidence: 95%
“…Contrary to what has been done for the static meniscus computation [4], we will not use here an energetic approach to establish the variational formulation describing the linear dynamic behavior of an inviscid and incompressible liquid with surface tension. It is easier here to directly write the variational formulation from the linear dynamic local equations of the problem, obtained by linearization of the classical motion equations of an inviscid incompressible fluid with capillarity with respect to the static equilibrium position that has been determined previously.…”
Section: Local Equationsmentioning
confidence: 98%
See 3 more Smart Citations